Beyond play: a comparative study of multi-sensory and traditional toys in child education - Fan, Yijun; Chong, Daphne Khee; Li, Yuanzhe (Frontiers in Education, 2024)
As educational paradigms evolve, the integration of multi-sensory theory into the design of children's educational toys presents a promising avenue for enhancing learning experiences. This paper explores the efficacy of multi-sensory toys in improving children's attraction, interest, and learning efficiency through a systematic review and a pilot empirical study. The study specifically assesses the hypothesis that multi-sensory educational toys significantly increase children's engagement and learning outcomes compared to traditional toys. Conducted with a diverse group of children aged 3 to 6 in Guangzhou and Shenzhen, China, the research employs both quantitative and qualitative methodologies, including engagement metrics and observational studies. The findings suggest that multi-sensory toys not only hold the potential to augment learning experiences but also require careful consideration of individual learning styles and preferences. The paper concludes with a discussion on the implications for future research and toy design, emphasizing the need for continued innovation and personalization in the development of educational toys to cater to the multifaceted needs of young learners.